Pemuda Yang Lari Telanjang: Teologi Kesempatan Kedua Dalam Kisah Yohanes Markus - Darmaka, Benediktus James Widya; Setiawan, Tjutjun (JURNAL KADESI, 2026)
This study examines the theological significance of the young man who fled naked in Mark 14:51-52 and explores the concept of second-chance theology through the life of John Mark. The problem underlying this research is that the brief narrative of the anonymous young man in the Gospel of Mark is often overlooked in biblical interpretation, despite its potential theological implications regarding failure, restoration, and discipleship. The purpose of this study is to analyze the narrative identity of the young man, commonly associated with John Mark, and to investigate how his life trajectory reflects God’s redemptive work through second chances. This research employs a qualitative approach using biblical narrative analysis, literary criticism, and theological reflection based on canonical texts such as Mark 14:51-52, Acts 13:13, Acts 15:36-40, Colossians 4:10, and 2 Timothy 4:11, supported by historical and theological literature. The analysis reveals that the Gospel writer intentionally preserved the embarrassing episode of the fleeing young man as a theological testimony of transformation. The findings indicate that John Mark’s journeyfrom failure in Gethsemane, desertion in missionary work, to restoration and recognition by apostolic leaders—illustrates the dynamic process of spiritual formation through grace and mentorship. The novelty of this research lies in interpreting Mark 14:51-52 not merely as a historical detail but as a narrative self-disclosure that frames the Gospel of Mark within a theology of restoration and second chances. Ultimately, this study concludes that the story of John Mark demonstrates that personal failure does not disqualify individuals from divine calling but may become the starting point of transformative ministry.